the body as potency and experience in early childhood: possible dialogues between philosophy and education - buss-simão, márcia (childhood & philosophy, 2013)
The present text attempts to construct a dialogue between Philosophy for Children and Childhood Education. Beyond its theoretical contribution, it explores their connections in observed situations during a doctoral research project in which the relations between space and time are intertwined with those of the body, through young children’s experiences of suffering small bruises, or what they call their “boo-boos.” Two particularities of those relations can be observed: first, that children perceive the body as an experience contextualized within the social and material world—that is, they don’t perceive their bodies as separated from the spaces they inhabit. A second particularity is that these relations invoke the possibility of time as aión–a constitution of time that is intertwined with people, spaces, places and actions in which these children undergo evident relations, emotions and encounters. Following these reflections, I introduce other situations in which children are expressing feelings and emotions, as well reflecting on situations involving their excreta—their “slime” and “snot”—as opportunities for thinking about the relations between body, childhood and education. If we begin with an understanding of childhood as experience–as an event that breaks with history–we are obliged to consider its implications for a childhood of education, and not only an education of childhood. This necessity may seem simple, but it requires another “look”– it requires us to “throw away” or at least to problematize part of our story, in order to make thinking possible in the context of others orders, others values, and finally, another education. It leads us to consider a form of education in which we look not only at the developmental processes of children, but also at their knowledge, their productions, their manifestations, their preferences, their interactions, and in particular their experiences.